72=3(3z)

Simple and best practice solution for 72=3(3z) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72=3(3z) equation:


Simplifying
72 = 3(3z)

Remove parenthesis around (3z)
72 = 3 * 3z

Multiply 3 * 3
72 = 9z

Solving
72 = 9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-9z' to each side of the equation.
72 + -9z = 9z + -9z

Combine like terms: 9z + -9z = 0
72 + -9z = 0

Add '-72' to each side of the equation.
72 + -72 + -9z = 0 + -72

Combine like terms: 72 + -72 = 0
0 + -9z = 0 + -72
-9z = 0 + -72

Combine like terms: 0 + -72 = -72
-9z = -72

Divide each side by '-9'.
z = 8

Simplifying
z = 8

See similar equations:

| 9(g-5h)= | | 10x-9y=2 | | 15x+7x-2=0 | | x+x+74=180 | | f(x)=3x^2+5x-7 | | 30=22.5/r | | (7x+3)(2x+6)=0 | | y=-x^2-10x+25 | | 10(b+4c)= | | 3x+34=9x-2 | | 1/(2sin(2x) | | 89-73=27y-31y | | 2x-(-4)=212 | | 2a+7=51 | | 2v-2=3v+15 | | 0.4n-1=35 | | 5x^2-7=49 | | 4b+36=9b+66 | | 4p-6=2p+4 | | (2x+4)+(3x^2-5x-3)=0 | | 0=-12p | | .5x^2-2x+3=0 | | -(4y+1)-(3y-8)=-1 | | 3x^2+11+5=0 | | 12=7/10g=44 | | 10(x+4)-2x=4x+2(2x+10)+20 | | 4e^3x=20 | | 4x^2+4x-17=0 | | 11(8r+3)2(9-6r)= | | 16n^2-161n=-5n^2-280 | | 9x^2-12x-8=0 | | -5x-30=3(x+4) |

Equations solver categories